Unions and Collective Bargaining in the Wake of the Great Recession - John T. Addison; Pedro Portugal; Hugo Vilares (Institute for the Study of Labor (IZA), 2015)
This paper provides the first definitive estimates of union density in Portugal, 2010-2012, using a unique dataset. The determinants of union density at firm level are first modeled. Next, we draw upon a very recent study of the union wage premium to provide summary estimates of the union wage gap for different ranges of union density. Since these estimates fully reflect the reality of an industrial relations system in which collective agreements are extended to nonunion workers and firms, the final issue examined is contract coverage. Although there has occurred a pronounced fall in the number of new extension agreements in recent years, this decline has been uncritically linked with a fall in coverage. We show that the number of workers covered by new and existing agreements has been largely unaffected by economic crisis. The reduced frequency of new agreements and extensions is viewed as an aspect of downward nominal wage rigidity in deflationary times (the counterpart of "upward nominal wage rigidity" in more normal times) rather than the immediate expression of a crisis in collective bargaining per se.
Keywords: J31; J52; J53; 330; collective bargaining; union density; collective agreement coverage; union wage premium; nominal wage rigidity; Portugal